STRATEGI PEREMPUAN KEPALA KELUARGA (PEKKA) DALAM MENCIPTAKAN KEMANDIRIAN EKONOMI KELUARGA DI DESA GESI KECAMATAN GESI KABUPATEN SRAGEN - Ramadhan Prasetya Wibawa; Liana Vivin Wihartanti (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2018)
This study aims to examine the strategies of female household heads (PEKKA) in creating family economic independence in Gesi Village, Gesi Subdistrict, Sragen Regency. The study used a descriptive qualitative approach. A total of 32 female heads of household and all of them were respondents. Data collection uses observation techniques, structured interviews, and documentation. Data analysis uses stages of data collection (data collection), data reduction (data reduction), presenting data display data), grouped data, drawing conclusions (using conclusions) and using data validity techniques triangulation of sources, time, and techniques. The results of the study showed that female household heads (PEKKA) in creating family economic independence in Gesi Village, Gesi Subdistrict, Sragen Regency through strategy: First, to build a strengthening of village community groups by joining PKK, Creative Business Groups in Gesi Village. Second, building capital gains through village business group savings and loans cooperatives. Third, building an information network with a technology-based outside world is still lacking. Fourth, to build business networks in rural areas based on village partners.Keywords: Strategy, PEKKA, Family Economic Independence